2005
DOI: 10.1074/jbc.m505268200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Statin-mediated Inhibition of Small G-protein Function

Abstract: 3-Hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) have been reported to reduce the risk of Alzheimer disease. We have shown previously that statins inhibit a ␤-amyloid (A␤)-mediated inflammatory response through mechanisms independent of cholesterol reduction. Specifically, statins exert anti-inflammatory actions through their ability to prevent the isoprenylation of members of the Rho family of small G-proteins, resulting in the functional inactivation of these G-proteins. We report that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(190 citation statements)
references
References 67 publications
12
176
0
2
Order By: Relevance
“…For instance, our laboratory and several others have recently unraveled the role of RhoA/ROCK in vascular endothelial growth factor (VEGF) signaling, an important mediator of microvascular complications of diabetes (34,35). We determined that VEGF-induced glo- by their inhibitory effects on RhoA/ROCK signaling (28,32,38). Indeed, we and others have previously shown that the inhibitory effects of statins on RhoA/ROCK signaling pathways may play an important role in the pleiotropic effects of statins (31,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our laboratory and several others have recently unraveled the role of RhoA/ROCK in vascular endothelial growth factor (VEGF) signaling, an important mediator of microvascular complications of diabetes (34,35). We determined that VEGF-induced glo- by their inhibitory effects on RhoA/ROCK signaling (28,32,38). Indeed, we and others have previously shown that the inhibitory effects of statins on RhoA/ROCK signaling pathways may play an important role in the pleiotropic effects of statins (31,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence also suggests that the essential role for protein prenylation is for optimal interaction of specific G-proteins, such as Rac1, with their regulatory proteins, such as Rho GDI (33,40,41). It is well established that GDI plays a regulatory role in membrane targeting of the active GTP-bound Rac1, as well as sequestration of the GDP-bound (inactive form) of Rac1 (4).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary antimouse and anti-rabbit antibodies either peroxidasecoupled or 35 S-labeled were from GE Healthcare Life Sciences (Freiburg, Germany). ECL detection reagent was from Pierce; methyl-β-cyclodextrin (MβCD), Zaragozic acid A, mevalonate, and lovastatin were from Sigma-Aldrich (Germany).…”
Section: Methodsmentioning
confidence: 99%